Mesoporous Films and Polymer Brushes Helping Each Other To Modulate Ionic Transport in Nanoconfined Environments. An Interesting Example of Synergism in Functional Hybrid Assemblies - Calvo, Alejandra (2009)
Rational design of fully synthetic platforms displaying active control over ionic transport in close resemblance to biological systems represents an ongoing challenge in molecular materials science. Here, we demonstrate that the synergism arising from the chemistries involved in mesoporous films and polymer brushes is a key enabler to next-generation ?smart? nanofilters capable of mimicking the gating functions of specific biological channels. Hybrid functional assemblies constituted of mesoporous silica films modified with polyzwitterionic brushes are able to discriminate and gate the transport of cations while the passage of anionic species is precluded. The synthetic membranes behave as proton-gated cation-selective platforms mimicking the functioning of acid-sensing ion channels encountered in the neurons of the central nervous system. We believe that this experimental evidence will stimulate further multidisciplinary work across the boundaries of materials chemistry to attain new functional nanostructured interfaces with transport properties so far believed to be exclusive features of biological channels.